2006
DOI: 10.2307/3844774
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects on Demography: A Long-Term Experimental Study of Testosterone's Effects on Fitness

Abstract: Understanding physiological and behavioral mechanisms underlying the diversity of observed life-history strategies is challenging because of difficulties in obtaining long-term measures of fitness and in relating fitness to these mechanisms. We evaluated effects of experimentally elevated testosterone on male fitness in a population of dark-eyed juncos studied over nine breeding seasons using a demographic modeling approach. Elevated levels of testosterone decreased survival rates but increased success of prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
137
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(145 citation statements)
references
References 0 publications
6
137
1
1
Order By: Relevance
“…Testosterone mediates behaviors that constitute mating effort, including singing, aggression, courtship, mate guarding, and pursuit of extra-pair matings. By facilitating mating effort, elevated testosterone concentrations can increase both within-pair and extra-pair mating success in male birds (Raouf et al, 1997;Reed et al, 2006). However, high testosterone concentrations can also reduce survival (Moss et al, 1994;Redpath et al, 2006;Reed et al, 2006).…”
Section: Testosterone In Alaska Malesmentioning
confidence: 99%
See 4 more Smart Citations
“…Testosterone mediates behaviors that constitute mating effort, including singing, aggression, courtship, mate guarding, and pursuit of extra-pair matings. By facilitating mating effort, elevated testosterone concentrations can increase both within-pair and extra-pair mating success in male birds (Raouf et al, 1997;Reed et al, 2006). However, high testosterone concentrations can also reduce survival (Moss et al, 1994;Redpath et al, 2006;Reed et al, 2006).…”
Section: Testosterone In Alaska Malesmentioning
confidence: 99%
“…By facilitating mating effort, elevated testosterone concentrations can increase both within-pair and extra-pair mating success in male birds (Raouf et al, 1997;Reed et al, 2006). However, high testosterone concentrations can also reduce survival (Moss et al, 1994;Redpath et al, 2006;Reed et al, 2006). Further study is needed to determine if the testosterone pattern observed in Alaska males contributes to the lower annual survival exhibited by this population.…”
Section: Testosterone In Alaska Malesmentioning
confidence: 99%
See 3 more Smart Citations